2014
DOI: 10.1016/j.soilbio.2014.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The match between microbial community structure and soil properties is modulated by land use types and sample origin within an integrated agroecosystem

Abstract: It is of global concern to adopt measures to mitigate land degradation caused by agricultural production systems. One of the strategies proposed is to replace degraded pastures with agrosilvopastoral systems which integrate three different land-use types: crop production, livestock pasture and forestry plantation (denoted iCLF). However, little is known about the differences between iCLF and other land use types in terms of soil microbial community structure. Distance matrices based on individual soil chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 48 publications
2
9
0
6
Order By: Relevance
“…Furthermore, at this low altitude, the highest amount of the nutrients K and P and an increase in pH were recorded. Generally, the availability of these nutrients reflects a lesser colonization of AMF in plant species and lower spore density (Abbott and Robson 1991), corroborating the hypothesis that plant species benefit from the symbiosis with AMF in low fertility environments (Berbara et al 2006;Miranda 2008;Moreira et al 2010;Lisboa et al 2014).…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, at this low altitude, the highest amount of the nutrients K and P and an increase in pH were recorded. Generally, the availability of these nutrients reflects a lesser colonization of AMF in plant species and lower spore density (Abbott and Robson 1991), corroborating the hypothesis that plant species benefit from the symbiosis with AMF in low fertility environments (Berbara et al 2006;Miranda 2008;Moreira et al 2010;Lisboa et al 2014).…”
Section: Discussionsupporting
confidence: 66%
“…These iCLFs are designed to have a different microbial structure from that of degraded pastures due to the greater diversity of their microbial community. However, the structure of this community is rarely investigated in integrated systems such as the iCLF, especially in the tropics (Lisboa et al, 2014). Thus, little information is available on the effects of increased species diversity on soil biological quality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the real factors were easily masked by other dependent factors. Second, the studies were conducted under different land use type in broad region which possibly could produce the various relationships between microbial communities and soil properties (Lisboa et al, 2014;Williams et al, 2013). Due to the decrease in bacteria, the fungal/bacterial ratio increased significantly after conversion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The different relationships between microbial communities and soil properties are mainly affected by land use type and land use history (Lisboa et al, 2014) and has been shown to be site-specific (Williams et al, 2013). The development of different plant species associated with land use conversion would have different influences on soil microbial communities in the rhizosphere, which depends on the differences in the quantity and quality of carbon resources different plant species produce (Sanon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%